Description of Atrocalopteryx fasciata spec. nov. from Yunnan, China (Odonata: Calopterygidae) - Yang, Guo-Hui; Hämäläinen, Matti; Zhang, Hao-Miao (Zootaxa, 2014)
Atrocalopteryx fasciata Yang, Hämäläinen & Zhang, spec. nov. (holotype ♂, from China, Yunnan, Dehong, Yingjiang, deposited at Odonata Collection of College of Agriculture and Life Sciences, Dali University, Dali, Yunnan, China) is described and illustrated from the male sex. It is compared with Atrocalopteryx laosica (Fraser, 1933).